Management of asthma in childhood: study protocol of a systematic evidence update by the Paediatric Asthma in Real Life (PeARL) Think Tank. Issue 7 (2nd July 2021) - Mathioudakis, Alexander G; Miligkos, Michael; Boccabella, Cristina; Alimani, Gioulinta S; Custovic, Adnan; Deschildre, A; Ducharme, Francine Monique; Kalayci, Omer; Murray, Clare; Garcia, Antonio Nieto; Phipatanakul, Wanda; Price, David; et al.
Abstract : Introduction: Clinical recommendations for childhood asthma are often based on data extrapolated from studies conducted in adults, despite significant differences in mechanisms and response to treatments. The Paediatric Asthma in Real Life (PeARL) Think Tank aspires to develop recommendations based on the best available evidence from studies in children. An overview of systematic reviews (SRs) on paediatric asthma maintenance management and an SR of treatments for acute asthma attacks in children, requiring an emergency presentation with/without hospital admission will be conducted. Methods and analysis: Standard methodology recommended by Cochrane will be followed. Maintenance pharmacotherapy of childhood asthma will be evaluated in an overview of SRs published after 2005 and including clinical trials or real-life studies. For evaluating pharmacotherapy of acute asthma attacks leading to an emergency presentation with/without hospital admission, we opted to conduct de novo synthesis in the absence of adequate up-to-date published SRs. For the SR of acute asthma pharmacotherapy, we will consider eligible SRs, clinical trials or real-life studies without time restrictions. Our evidence updates will be based on broad searches of Pubmed/Medline and the Cochrane Library. We will use A MeaSurement Tool to Assess systematic Reviews, V.2, Cochrane risk of bias 2 and REal Life EVidence AssessmeNt Tool to evaluate the methodological quality of SRs, controlled clinical trials and real-life studies, respectively. Next, we will further assess interventions for acute severe asthma attacks with positive clinical results in meta-analyses. We will include both controlled clinical trials and observational studies and will assess their quality using the previously mentioned tools. We will employ random effect models for conducting meta-analyses, and Grading of Recommendations Assessment, Development and Evaluation methodology to assess certainty in the body of evidence. Ethics and dissemination: Ethics approval is not required for SRs. Our findings will be published in peer reviewed journals and will inform clinical recommendations being developed by the PeARL Think Tank. PROSPERO registration numbers: CRD42020132990, CRD42020171624.